STUDI KOMPARATIF KUALITAS HIDUP IBU HAMIL REMAJA BERDASARKAN STATUS - Dewi Hanifah (JKM (Jurnal Kebidanan Malahayati), 2021)
Background: Teenage pregnancy is a high-risk pregnancy and can cause various social, medical and physical health problems. During teenage pregnancy, there are physical, mental and social changes which are dimensions of quality of life. Many factors related to quality of life including demographic status.Objective: To determine the quality of life of adolescent pregnant women and compare the quality of life based on demographic statusMethods: This research is a comparative study conducted at the Sukabumi PONED Public Health Center in October 2019 – November 2020. The population in the study was pregnant women aged less than 20 years, the sample in this study was 34 people with a sampling technique using accidental sampling. The quality of life instrument uses the Short Form-36 (SF 36). Quality of life outcomes were compared based on demographic characteristics, namely education, parity, gestational age, marital status, pregnancy status. Data that were normally distributed were analyzed using the t test, while data that were not normally distributed were analyzed using the Mann Whitney test. Test the normality of the data using the Kolmogorov Smirnov test for the quality of life variable.Results: The average quality of life scores for the domains of physical function, pain, general health, energy, social function, emotional roles, mental health, physical health components, mental health components have an average value above 50. There are differences in scores in several quality domains. life in the respondent group based on gestational age, pregnancy status and marital status with p <0.05.Conclusion: There are differences in several domains of quality of life based on gestational age, pregnancy status and marital status.Keywords: Quality of Life, Teenage Pregnancy